Survey of publicly available reports on advanced persistent threat actors. Issue 72 (January 2018) - Lemay, Antoine; Calvet, Joan; Menet, François; Fernandez, José M.
Abstract: The increase of cyber attacks for the purpose of espionage is a growing threat. Recent examples, such as hacking of the Democratic National Committee and indicting by the FBI of Chinese military personnel for cyber economic espionage, are testaments of the severity of the problem. Unfortunately, research on the topic of Advanced Persistent Threats (APT) is complicated due to the fact that information is fragmented across a large number of Internet resources. This paper aims at providing a comprehensive survey of open source publications related to APT actors and their activities, focusing on the APT activities, rather than research on defensive or detective measures. It is intended to serve as a quick reference on the state of the knowledge of APT actors, where interested researchers can find what primary sources are most relevant to their research. The paper covers publications related to around 40 APT groups from multiple regions across the globe. A short summary of the main findings of each publication is presented.